Investigating the care needs of those with endometriosis: Are we listening to the patients?. (16th October 2019) - Steele, Emma; Bush, Deborah; Healey, Martin; Rapsey, Charlene M.; Peate, Michelle; Girling, Jane E.
Abstract : What do women with endometriosis need? What are the things that would make their lives easier? Where are the gaps in their care? Questions like these can only be answered by women themselves. The development of an unmet needs survey for women with endometriosis would facilitate the design of patient‐centred interventions to meet these needs and ultimately improve quality of life.